2017
DOI: 10.1002/2016gl072305
|View full text |Cite
|
Sign up to set email alerts
|

Increased atmospheric ammonia over the world's major agricultural areas detected from space

Abstract: This study provides evidence of substantial increases in atmospheric ammonia (NH3) concentrations (14 year) over several of the worlds major agricultural regions, using recently available retrievals from the Atmospheric Infrared Sounder (AIRS) aboard NASA's Aqua satellite. The main sources of atmospheric NH3 are farming and animal husbandry involving reactive nitrogen ultimately derived from fertilizer use; rates of emission are also sensitive to climate change. Significant increasing trends are seen over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
253
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(285 citation statements)
references
References 51 publications
17
253
3
1
Order By: Relevance
“…We summarize in Table 1 (Xu et al, 2016;Kang et al, 2016), consistent with trends in atmospheric NH 3 concentration observed from satellites (Warner et al, 2017;Fu et al, 2017). Fertilizer application and livestock waste are the two largest NH 3 sources, together accounting for more than 82 % of the total anthropogenic emissions over China (Table 1).…”
Section: Previous Bottom-up Estimates Of Chinese Nh 3 Emissionsmentioning
confidence: 52%
See 1 more Smart Citation
“…We summarize in Table 1 (Xu et al, 2016;Kang et al, 2016), consistent with trends in atmospheric NH 3 concentration observed from satellites (Warner et al, 2017;Fu et al, 2017). Fertilizer application and livestock waste are the two largest NH 3 sources, together accounting for more than 82 % of the total anthropogenic emissions over China (Table 1).…”
Section: Previous Bottom-up Estimates Of Chinese Nh 3 Emissionsmentioning
confidence: 52%
“…Satellite observations of atmospheric NH 3 concentration have been emerging in recent years. These satellite instruments include the Tropospheric Emission Spectrometer (TES) (Beer et al, 2008;Shephard et al, 2011), the Infrared Atmospheric Sounding Interferometer (IASI) (Clarisse et al, 2009;Van Damme et al, 2015), the Atmospheric Infrared Sounder (AIRS) (Warner et al, 2016(Warner et al, , 2017, and the Cross-track Infrared Sounder (CrIS) , providing increasingly rich datasets to understand the spatial and temporal variability of NH 3 in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…For the national distribution captured at a resolution of 2 × 2.5 • , the highest values were observed in the NCP, the entire provinces of Henan and Hubei, and the north of Hunan Province, which shows a high population density and increasing economic expansion, reflecting the slightly different emission characteristics of sulfate and ammonium. Previous studies have concluded that these high regional concentrations were caused by agricultural activities [49][50][51] …”
Section: Evaluation Of Satellite-estimated Chemical Componentsmentioning
confidence: 99%
“…The ammonia rich plumes from those areas drive most of the nitric acid into the particle phase, 5 resulting in high PM 2.5 concentrations in those regions (Neuman et al, 2003;Baek and Aneja, 2004). Recent studies have also shown that atmospheric ammonia has increased during the last two decades, a trend that is expected to continue as a result of global warming, increasing agricultural activity and intensifying fertilizer use due to growing population Amann et al, 2013;Warner et al, 2017).…”
Section: Introductionmentioning
confidence: 99%